Peroxynitrous Acid Generated In Situ from Acidified H2O2 and NaNO2. A Suitable Novel Antimicrobial Agent? - Martina Balazinski; Ansgar Schmidt-Bleker; Jörn Winter; Thomas von Woedtke (MDPI AG, 2021)
Peroxynitrite (ONOO−) and peroxynitrous acid (ONOOH) are known as short acting reactive species with nitrating and oxidative properties, which are associated with their antimicrobial effect. However, to the best of our knowledge, ONOOH/ONOO- are not yet used as antimicrobial actives in practical applications. The aim is to elucidate if ONOOH generated in situ from acidified hydrogen peroxide (H2O2) and sodium nitrite (NaNO2) may serve as an antimicrobial active in disinfectants. Therefore, the dose-response relationship and mutagenicity are investigated. Antimicrobial efficacy was investigated by suspension tests and mutagenicity by the Ames test. Tests were conducted with E. coli. For investigating the dose-response relationship, pH values and concentrations of H2O2 and NaNO2 were varied. The antimicrobial efficacy is correlated to the dose of ONOOH, which is determined by numerical computations. The relationship can be described by the efficacy parameter W, corresponding to the amount of educts consumed during exposure time. Sufficient inactivation was observed whenever W ≥ 1 mM, yielding a criterion for inactivation of E. coli by acidified H2O2 and NaNO2. No mutagenicity of ONOOH was noticed. While further investigations are necessary, results indicate that safe and effective usage of ONOOH generated from acidified H2O2 and NaNO2 as a novel active in disinfectants is conceivable.